The influence of sports drinks on the occurrence of erosion among athletes - a narrative review - Pietruszka, Wiktoria; Musyt, Wiktoria; Klasicki , Przemysław; Potrykus, Maria; Dudziński , Szymon (Quality in Sport, 2025)
Introduction: Athletes widely consume sports drinks to support hydration and performance. However, their acidic composition and frequent intake have raised growing concerns about their potential role in dental erosion, a condition that irreversibly damages the hard tissues of the teeth. Athletes may be particularly vulnerable due to exercise-induced changes such as reduced salivary flow and altered oral pH. Aim of the Study: This narrative review aims to explore the relationship between the consumption of sports drinks and the prevalence of dental erosion among athletes, and to discuss the underlying mechanisms and preventive strategies. Materials and Methods: This review is based on a comprehensive analysis of scientific literature obtained from databases such as PubMed, Scopus, and Google Scholar, with a focus on the composition of sports drinks, erosion risk factors, salivary changes during physical exertion, and clinical observations among athletic populations. Conclusions: Frequent consumption of sports drinks, especially in combination with physical activity-related factors like dehydration and mouth breathing, significantly increases the risk of erosive tooth wear in athletes. Preventive strategies should emphasize education, dietary counseling, and fluoride-based interventions. Early recognition and personalized dental care are essential to reduce long-term damage and preserve athletes’ oral health.